Metabolic Function of a Suboptimal Transplanted Islet Mass in Nonhuman Primates on Rapamycin Monotherapy - Scott A. Soleimanpour M.D. (Cell Transplantation, 2012)
Although islet transplantation may restore insulin independence to individuals with type 1 diabetes mellitus, most have abnormal glucose tolerance. We asked whether the defective glucose tolerance is due to inadequate β-cell mass or to impaired insulin sensitivity. We performed metabolic studies on four cynomolgus primates before inducing diabetes with streptozotocin (STZ), then again 2–3 weeks after restoring insulin independence via intrahepatic islet transplantation utilizing a calcineurin inhibitor-free immunosuppressive regimen (induction with rabbit antithymocyte globulin and maintenance therapy with rapamycin). Engrafted β-cell mass was assessed by acute insulin and C-peptide responses to glucose (AIR glu and ACR glu ) and arginine (AIR arg and ACR arg ). Insulin sensitivity (S I ) was determined in naive and transplanted primates from an intravenous glucose tolerance test using the minimal model. α-Cell function was determined by the acute glucagon response to arginine (AGR arg ). Glucose tolerance ( K g ) decreased from 4.1 ± 0.5%/min in naive primates to 1.8 ± 0.3%/min in transplanted primates ( p < 0.01). Following transplantation, AIR glu was 28.7 ± 13.1 μU/ml compared to 169.9 ± 43.1 μU/ml ( p < 0.03) in the naive condition, ACR glu was 14.5 ± 6.0 ng/ ml compared to 96.5 ± 17.0 ng/ml naive ( p < 0.01), AIR arg was 29.1 ± 13.1 μU/ml compared to 91.4 ± 28.2 μU/ml naive ( p < 0.05), and ACR arg was 1.11 ± 0.51 ng/ml compared to 2.79 ± 0.77 ng/ml naive ( p < 0.05). S I did not differ from naive to posttransplant states. AGR arg was reduced in transplanted primates (349 ± 118 pg/ml) when compared to both naive (827 ± 354 pg/ml) and post-STZ diabetic primates (1020 ± 440 pg/ml) ( p < 0.01 for both comparisons). These data suggest that impaired glucose tolerance observed in islet transplant recipients is secondary to low functional β-cell mass and not to insulin resistance shortly after transplant. Furthermore, improved glycemic control achieved via islet transplantation over the diabetic state might be attained, in part, via reduced glucagon secretion.